Exploring the optimal placement of Natural Flood Management (NFM) in different catchment configurations - Legarda Garzon, Luis Fernando (2021)
Fluvial flooding causes significant economic, environmental and social losses, which are predicted to increase in the future due to climate change, land use change and increased urbanisation. To mitigate flooding, focus has moved from hard engineering and structural defences to risk reduction utilising natural processes, particularly tree planting to slow the flow. Whilst Natural Flood Management (NFM) has received a lot of attention, most research has focused on modelling small, upland catchments in the UK, with limited evidence demonstrating where and when NFM interventions are likely to be most effective. Therefore, I aimed to use a coupled hydraulic-hydrological model to explore how the morphology of catchments, intensity of rainfall, and the spatial configuration and coverage of NFM (tree cover), effects peak flows and lag times. The ultimate goal was to ascertain where in a catchment tree cover could be optimally placed to maximise reductions in peak flows.